Danshen-Honghua Ameliorates Stress-Induced Menopausal Depression in Rats - Simeng Gu; Yao Ma; Kemin Ge; Ruifang Nie; Erxi Wu; Yang Li (Neural Plasticity)
Objective. Previously, we have shown that Danshen-Honghua (DSHH) for cognitive deficits after ischemia induced impairments of the hippocampus. Here, we investigate the effects of DSHH on stress-induced depression in menopausal rats. Methods. A rat model with menopausal depression was established with bilateral ovariectomies in female SD rats followed by chronic mild stress treatment for 21 days. 40 rats were randomly divided into the sham surgery group (sham surgery and no stress treatment), surgery group (surgery with no stress treatment), surgery/stress group (surgery and stress treatment), fluoxetine group (2.4 mg·kg−1, with surgery and stress treatment), and DSHH group (35 g·kg−1, with surgery and stress treatment). The rats in the last two groups were treated with stresses together with intragastric drug administration for three weeks after the surgery. Then open-field locomotor scores and sucrose intake were tested for behavior changes. Also, the levels of norepinephrine (NE), dopamine (DA), serotonin (5-HT), and cortisone were determined by high-performance liquid chromatography (HPLC). Serum estradiol (E2), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) were determined by radioimmunoassay. Results. The results of open-field locomotor scores, sucrose intake in both the fluoxetine group and DSHH group, were significantly higher than those of the surgery/stress group (P<0.01). Serum LH, FSH, and cortisone levels in both the DSHH group and fluoxetine group were significantly lower than those in the surgery/stress group (P<0.01). Serum E2 levels in these groups were slightly increased in these medicine groups (P<0.01). The monoamine levels in the DSHH group were much higher than those in the surgery/stress group (P<0.01). Conclusion. DSHH can ameliorate stress-induced depressed syndromes in the surgery/stressed rats via regulating LH and FSH levels as well as monoamine levels.